Audit Quality and IPO Underpricing - Tengku Rahimah, Tengku Arifin (2010)
This study extends the previous researchers on the underpricing by examining the association between audit quality and level of underpricing. The data are from 152 companies listed on Bursa Malaysia from the period of 2005 to 2009. The level of underpricing in Malaysia is 14.77% during the period. The study specifically investigates the impact of audit quality proxied by Big 4 audit firms, industry-specialized audit firms and international audit firms. The finding of this study indicates that Big 4 auditor including its local affiliates is significantly and positively associated with underpricing. However, if the affiliates are excluded in measuring the Big 4 auditor, it is significantly and negatively associated with underpricing. While the others proxies (industry-specialized auditor and international auditor) are negatively associated with underpricing. The result implies that Malaysian investors differentiate the services provided by Big 4 and local firms. They assume the quality of the audit to be lower if there is an involvement by the local firms in the audit processes. Besides, the underwriter reputation is also significantly associated with underpricing, indicating that the ex ante uncertainty do not reduce although the reputable underwriter is engaged by the IPO companies.